2020
DOI: 10.1093/ofid/ofaa583
|View full text |Cite
|
Sign up to set email alerts
|

Education of Infectious Diseases Fellows During the COVID-19 Pandemic Crisis: Challenges and Opportunities

Abstract: One of the many challenges that has befallen the Infectious Diseases and Graduate Medical Education communities during the coronavirus disease 2019 (COVID-19) pandemic is the maintenance of continued effective education and training of the future leaders of our field. With the remarkable speed and innovation that has characterized the responses to this pandemic, educators everywhere have adapted existing robust and safe learning environments to meet the needs of our learners. This paper will review distinct as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Third, we analyzed the summer term 2020, which already dates back several months, while modes and methods of online learning have rapidly evolved since the beginning of the pandemic. Hence, even more modern technologies are available and accepted for both undergraduate and postgraduate teaching [20][21][22][23]. Furthermore, course evaluation by the students was voluntary, leading to smaller number of respondents than students taking the respective exams.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we analyzed the summer term 2020, which already dates back several months, while modes and methods of online learning have rapidly evolved since the beginning of the pandemic. Hence, even more modern technologies are available and accepted for both undergraduate and postgraduate teaching [20][21][22][23]. Furthermore, course evaluation by the students was voluntary, leading to smaller number of respondents than students taking the respective exams.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we analyzed the summer term of 2020, which already dates back several terms, while modes and methods of online learning have rapidly evolved since the beginning of the pandemic. Hence, even more modern technologies are available and used in both undergraduate and postgraduate teaching [31][32][33][34][35]. Furthermore, course evaluation by the students was voluntary, leading to a smaller number of respondents than students taking the respective exams.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In order to identify published educational methods that integrate the above characteristics, a comprehensive review of articles from the general medical and pediatric literature was conducted using the MEDLINE database. The clinical learning models identified included the one-minute preceptor (OMP) five microskills method ( Neher et al, 1992 ), the SNAPPS (Summarize, Narrow, Analyze, Probe, Plan, Select) model of learner-centered precepting ( Wolpaw et al, 2003 ), the Aunt Minnie model of learning pattern recognition ( Cunningham et al, 1999 ), the RIME (Reporter, Interpreter, Manager, Educator) developmental framework for teaching/assessing clinical performance ( Pangaro, 1999 ), the PARTNER (Partner with learner, Assess, Reinforce, Teach, New knowledge, Execute, Review) framework ( Chirch et al, 2021 ; Miloslavsky et al, 2017 ), and preceptor teaching scripts ( Gonzalo et al, 2013 ; Irby et al, 2004 ). A recent Best Evidence Medical Education review of the effectiveness of clinical teaching strategies concluded that the OMP and SNAPPS models were the only strategies that consistently improved the clinical knowledge and skills of learners — a significant advantage over the other mentioned frameworks ( Pierce et al, 2020 ).…”
Section: Perspectivementioning
confidence: 99%